Comparative outcomes of thulium laser enucleation by prostate volume: a three-group analysis from a single-center study in Vietnam - Hoai Nam Tran; Van Hinh Tran; Viet Cuong Nguyen (African Journal of Urology)
Abstracts Purpose To evaluate the impact of prostate volume on the safety and efficacy of Thulium Laser Enucleation of the Prostate (ThuLEP) in treating benign prostatic enlargement (BPE) across different prostate volume groups. Materials and Methods This prospective study included 92 BPE patients who underwent ThuLEP, stratified into three groups based on prostate volume: Group A (< 50 ml), Group B (50–80 ml), and Group C ( >80 ml). Preoperative and postoperative functional outcomes, intraoperative parameters, and complications were analyzed and compared among the groups. Statistical analysis was performed using IBM SPSS Statistics 27. Results Operative time significantly increased with prostate size (Group C: 105 ± 32.74 min vs. Group A: 71.45 ± 33.87 min, p < 0.001). Enucleation time per ml of prostate tissue was most efficient in Group C (0.98 ± 0.55 min/ml, p < 0.001). Postoperative improvements in IPSS, Qmax, QoL, and PVR were significant across all groups, with no notable differences among the groups at 6 months (p > 0.05). The overall complication rate was low (11.96%), with major complications (Clavien-Dindo grade II or higher) accounting for only 6.52%. No significant differences in complication rates were observed among the groups. Conclusions ThuLEP demonstrated excellent safety and efficacy in treating BPE, regardless of prostate size. Larger prostates required longer operative times but achieved comparable functional outcomes with low complication rates. These findings support ThuLEP as a reliable and versatile surgical option for a wide range of prostate volumes.